A comparison between GATE and MCNPX for photon dose calculations in radiation protection using a male voxel phantom. (April 2019) - Cui, Tiantian; Li, Zhanpeng; Zhang, Shuyuan; Wang, Yidi; Chen, Dandan; Sun, Liang
Abstract: The purpose of this work was to validate GATE external photon beam dosimetry calculations in radiological protection. In this work, GATE Standard, Livermore and Penelope physics lists (PLs) and MCNPX were used to calculate fluence-dose conversion coefficients for Korean Typical MAN-2 (KTMAN-2) voxelized phantom. Six irradiation geometries, anterior–posterior (AP), posterior–anterior (PA), left lateral (LLAT), right lateral (RLAT), rotational (ROT) and isotropic (ISO) for monoenergetic photon beams from 10 keV to 10 MeV were simulated. Compared the simulation results between GATE and MCNPX, it was shown that the GATE results agreed well with MCNPX results with an average accuracy better than 2.24% for energies above 30 keV. Although good agreements were found for both GATE Standard and Penelope PLs and MCNPX, Livermore PL has better stability and it is slightly more accurate than Standard and Penelope PLs. Dosimetric results generated with GATE for the organs of KTMAN-2 are available as supplemental data. The results indicate that GATE could be safely used for external photon beam dosimetry. This makes GATE a viable option for Monte Carlo modelling of both imaging and absorbed dose in external radiological protection. Highlights: We compared GATE and MCNPX simulation predictions based on KTMAN-2 voxelized phantom. We found GATE Livermore PL fit better and shows more stability with MCNPX than Standard and Penelope PLs. We made the DICOM format allows export the detailed description of a phantom from MCMPX to GATE. The calculated results would be significance for analyzing the difference in dose conversion coefficients for Asian male.